Differential roles of prostaglandin E2 EP4 receptor on stromal cell populations for hematopoietic stem and progenitor cell function - Liu, Liqiong; Li, Hongge; Singh, Pratibha; Hoggatt, Jonathan; Pelus, Louis M. (Frontiers in Hematology, 2023)
Prostaglandin E2 (PGE2) signaling through its EP4 receptor regulates hematopoietic stem and progenitor cell (HSPC) functions. Here we generated mouse strains with conditional and inducible deletion of EP4 in stromal cell populations, including osteolineage cells, mesenchymal progenitor cells, perivascular stromal cells, and endothelial cells, to evaluate the role of EP4 in HSPC regulation through signaling in each of these niche cell populations. We found that EP4 deletion in different stromal cells had distinct effects on HSPC proliferation, long-term repopulating capacity, and the peripheral blood stem cell mobilization response. Lack of EP4 signaling in osteolineage cells increased HSPC number but impaired their long-term engraftment and mobilization. EP4 deletion in mesenchymal progenitor cells and endothelial cells reduced HSPC number and function, while EP4 deletion in perivascular stromal cells had sex-specific effects on HSPC engraftment. Our results demonstrate that PGE2/EP4 signaling in bone marrow stromal cells plays a significant and complex role in HSPC regulation, with both positive and negative effects depending on the stromal cell type.